GW151226: Observation of Gravitational Waves from a 22-Solar-Mass Binary Black Hole Coalescence - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Amer Physical Soc, 2016)
We report the observation of a gravitational-wave signal produced by the coalescence of two stellar-mass black holes. The signal, GW151226, was observed by the twin detectors of the Laser Interferometer Gravitational-Wave Observatory (LIGO) on December 26, 2015 at 03: 38: 53 UTC. The signal was initially identified within 70 s by an online matched-filter search targeting binary coalescences. Subsequent off-line analyses recovered GW151226 with a network signal-to-noise ratio of 13 and a significance greater than 5 sigma. The signal persisted in the LIGO frequency band for approximately 1 s, increasing in frequency and amplitude over about 55 cycles from 35 to 450 Hz, and reached a peak gravitational strain of 3.4(-0.9)(+0.7) x 10(-22). The inferred source-frame initial black hole masses are 14.2(-3.7)(+8.3) M-circle dot and 7.5(-2.3)(+2.3) M-circle dot, and the final black hole mass is 20.8(-1.7)(+6.1) M-circle dot. We find that at least one of the component black holes has spin greater than 0.2. This source is located at a luminosity distance of 440(-190)(+180) Mpc corresponding to a redshift of 0.09(-0.04)(+0.03). All uncertainties define a 90% credible interval. This second gravitational-wave observation provides improved constraints on stellar populations and on deviations from general relativity.